METAFORA DALAM LIRIK LAGU ANGGUN C SASMI - Bahanuddin, Sofianti; Hasbullah, Hasbullah (JURNAL ILMU BUDAYA, 2017)
This research aims to analyze the use of metaphorical language styles in songs. Because like poetry, the language used in the song is not the same as the language used when someone is conversing, often the language used in song lyrics is ambiguous and uses the style of the language. Based on this, the researchers are interested to discuss the use of language styles in song lyrics, but in this research, researchers focused on researching only on the style of metaphorical language with the title "Metaphors in the Lyrics of  the song Anggun C Sasmi (Semantic Analysis)". Data retrieval is done by using technique refer and note. The data have been collected and then analyzed using the supporting theories in this research. The theory used in this research is metaphorical and semantic style of language. Metaphor is a comparative language style that is divided into 4 types. While semantic theory is needed to analyze every metaphoric meaning contained in the lyrics of the song Anggun C Sasmi. From the analysis, the researchers collected 20 metaphorical data consisting of: (1) 8 forms of anthropomorphic metaphor, (2) 2 forms of animal metaphor, (3) 9 concrete-abstract metaphor form, and (4) 1 sinaesthetic metaphor form. The use of metaphorical language style in the songs Anggun C Sasmi aims to give the aesthetic effect also reinforces the message conveyed the songwriter.Key words: metaphor, semantic, song, aesthetic, meaning.